ANALISIS YURIDIS PERUBAHAN HAK ATAS TANAH DARI STATUS HAK GUNA USAHA MENJADI HAK PENGELOLAAN PADA KAWASAN EKONOMI KHUSUS SEI MANGKEI PT. PERKEBUNAN NUSANTARA III (PERSERO) - SHEILA ARSITYANI (PREMISE LAW JURNAL, 2016)
PT. Perkebunan Nusantara III (Persero) has to perform land acquisition in the area of 2,002.77 hectares at Sei Manmgke Village, Bosar Maligas Subdistrict, Simalungun District, which would be Specific Economy Area. Since the Leasehold is still attached to the land, PT. Perkebunan Nusantara III (Persero) amended the Leasehold to the Right to Manage in condition that the company filed the permit of Leasehold to the Land Office of North Sumatera. The result of the research showed that, the company filed a survey on the Leasehold area in the area of 2,002.77 hectares to the Land Office of North Sumatera. After the renunciation of rights was approved, the request of the Right to Manage was filed to the National Land Board of the Republic of Indonesia. The result was that the Head of the National Land Board of the Republic of Indonesia issued the Decree No. 27/HPL/BPN RI/2014 on the Approval of Giving the Right to Manage on the name of PT. Perkebunan Nusantara III (Persero), located in Medan for 4 (four) tracts of land, located in Simalungun District, North Sumatera on June 23, 2014. The changing process from the Leasehold to the Right to Manage in the Specific Economy Area Sei Mangke was constrained since the Layout of Simalungun District was not completed so that the Specific Economy Area did not have the layout, the constraint of the term of the change of the right, and internal and external constraint in that area. Keywords: Right to Manage, Leasehold, Specific Economy Area Sei Mangke, PT. Perkebunan Nusantara III (Persero)